Pengaruh Kebijakan Dividen dan Net Profit Margin (NPM) Terhadap Return Saham Perusahaan Transportasi di BEI 2020 -2023 - Amanda Sevani Angelica; Ana Ramadhayanti (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research was conducted on transportation companies on the Indonesia Stock Exchange (IDX) for the period 2020 - 2023 through the official IDX website. This study uses profitability ratios and market ratios, namely Net Profit Margin (NPM) and Dividend Payment Ratio (DPR). The purpose of this study was conducted to determine how influential Dividend Policy with the Dividend Payment Ratio (DPR) and Net Profit Margin (NPM) metrics is on the Stock Return of transportation companies on the Indonesia Stock Exchange (IDX) for the period 2020 - 2023. The analysis method used in this research is quantitative statistics by conducting descriptive statistical tests, classical assumption tests, multiple linear regression tests, and hypothesis testing as a tool in data analysis. This research data comes from financial statements, namely income statements and changes in equity of transportation companies listed on the Indonesia Stock Exchange (IDX) for the period 2020 - 2023. The results of the study partially both variables, namely Dividend Payment Ratio (DPR) and Net Profit Margin (NPM) have influence on Stock Returns. Keywords: Dividend Payment Ratio (DPR), Net Profit Margin (NPM), Stock Return.